Possibility of the Manager and the Members of the Board of the Subsidiary to Act in the Interests of the Group of Companies - Bakanauskas, Edvinas (Teisė, 2021)
According to the current legal regulation of Lithuanian companies, the manager and the members of the board of the subsidiary have a duty to act only in the interests of the subsidiary and do not have the opportunity to act in the interests of the group of companies. Meanwhile, the provisions of Section 16 of Chapter 15 of European Model Companies Act provide the possibility for the manager and the members of the board of the subsidiary to act in the interests of the group of companies. Accordingly, the present article analyses whether the current legal framework in Lithuania should be changed by providing the possibility for the manager and the members of the board of the subsidiary to act in the interests of the group of companies.